(untitled) (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2018)
The story is a story that has silenced women and has been broken from the birth of a history of women. Something similar happens with the history of technical education, most notably androcentric and patriarchal, in which women have been invisible or under the domination of men. The present article seeks, firstly, to recover from the history of Argentine education the training proposals aimed at women as the best way to legitimize sexual difference. As a result of the field work carried out in secondary technical schools in the province of Buenos Aires, the history of the segregation of women in schools created to form them in their "natural" attributes, is reconstructed and the curricula of the Professional Schools Of Women to show the essential representation in which these plans are sustained. Finally, we present some moments of the trajectories of women who chose to study and work in the technical school who express an experience of struggle to obtain the same recognition that the men in the educational field.